P142 IMPACT OF NEO-ADJUVANT CHEMOTHERAPY ON CARDIORESPIRATORY RESERVE, SARCOPENIA AND QUALITY OF LIFE IN OESOPHAGO-GASTRIC CARCINOMA. (23rd November 2019) - Navidi, M; Phillips, A; Griffin, M; Petrides, G; Perthen, J; Ali, T; Greystoke, A; Sinclair, R
Abstract: Background: The management of locally advanced oesophago-gastric (OG) adenocarcinoma in the UK includes three cycles of MAGIC protocol neoadjuvant chemotherapy (NAC). NAC may have a detrimental impact on fitness, quality of life and sarcopenia. Determination of the oxygen uptake at the anaerobic threshold (AT) by cardiopulmonary exercise testing (CPET) objectively measures cardiorespiratory reserve (fitness). AT can be used to predict perioperative risk. Sarcopenia is defined by decreased skeletal muscle mass and is a poor prognostic factor. Patients view their health by means of quality of life (QOL) rather than traditional clinical outcomes. This study was conducted to determine the impact of neoadjuvant chemotherapy on fitness, sarcopenia and quality of life following neoadjuvant chemotherapy. Methods: Patients with locally advanced OG adenocarcinoma were recruited. CPET, sarcopenia and QOL were measured before and following NAC. AT and peak oxygen uptake (VO2 Peak) were used to assess fitness. CT images at staging and upon completion of NAC were used to measure sarcopenia (muscle mass and function). EORTC QOL-Core 30 and QLQ-Oesophagogastric 25 questionnaires assessed QOL. Results: 31 patients with a median age of 65 (41-81) were recruited, 27 patients completed all three cycles of NAC. The results of pre and post NAC measured parameters are outlined in the table below. Pre NAC (+/-1SD) Post NAC (+/-1SD) P Value Anaerobic Threshold (ml/kg/min) 15.3(3.4) 11.9(2.5) <0.01 VO2 peak (ml/kg/min) 21.7(3.9) 17.5(3.0) <0.01 Mean Muscle Mass (cm 2 ) 162.7 (33.5) 151.2 (30.9) <0.001 Muscle Mass Index (cm 2 /m 2 ) 53.3 (9.5) 49.6 (9.5) <0.001 Mean Grip Strength (kg) 39.4 (6.6) 36.5 (6.5) <0.001 Global Health Status (QoL) 72.2(20.5) 59.3(25.3) 0.043 Physical Functioning 92.7(13.7) 79.7(17.7) <0.01 Cognitive Functioning 88.9(14.7) 78.7(2) 0.04 Fatigue 20.9(24.7) 41.3(28.9) <0.01 Conclusion: NAC significantly impacts fitness, sarcopenia levels and QOL. Preventing this reduction through development of 'prehabilitation' strategies, or optimising timing of surgery after recovery of the observed decline, may decrease perioperative risk, reduce postoperative complications and improve quality life. This should be the focus of future studies.